Factors affecting the Turkish accounting practices during the Republcian era - Uman, Onur. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This thesis is based on the assumption that the development of Turkish accounting practices do differ from the West European and North American ones. In the countries possessing a mercantilist past, followed by an industrial stage, generally the existance of stock markets, the nature and the size of their industry, past economic crisis, and independent accounting organizations can be identified as the main factors for the development of accounting practices. Since Turkey had not possessed most of these factors (starting from 19th century till 1980s) the evolution of the above mentioned practices had to take a different route. The thesis’ hypothesis is that the Turkish accounting practices were mainly shaped by the laws instead of market forces. To support the hypothesis an analysis of the market forces in different periods of the last century has be done and it is concluded that none of them showed enough economic sophistication nor a significant size to become a force to push the development of accounting in Turkey. Instead the laws, mainly tax laws, tried to require double-entry bookkeeping from an underdeveloped economy. The emerging private sector started to challenge this model by depending more and more to modern bookkeeping and reporting, starting 1980s, and the international factors of 1990s added momentum to that change. Still, accounting practices are heavily influenced by legal procedures but their evolution is getting more and more affected by the market forces.
Keywords: Accounting -- Turkey.